Prevalence and predictors of stress in nursing technicians in the state of Sergipe in the period of the Covid-19 pandemic - Rocha de Souza, Luana; Lima Barreto, Manuela Naiane; Calazans Batista, Jefferson Felipe; Freitas de Jesus, Carla Viviane; Lima Batalha de Andrade, Renata; Oliveira Lima, Sônia (JRG Journal of Academic Studies, 2023)
Introduction: The pandemic demanded exhaustive work shifts from nursing professionals, generating fatigue and stress. Objective: To identify the prevalence and predictors of stress in nursing technicians in the state of Sergipe in the period of the COVID-19 pandemic. Methodology: Cross-sectional, quantitative study, with 150 nursing technicians and assistants who worked with patients with COVID-19, in Sergipe (2021-2022), conducted via Google Forms, through Informed Consent Form (ICF). The sociodemographic and professional profile was evaluated, and the Lipp’s Inventory of Stress Symptoms for Adults - ISSL was applied. The chi-square or Fisher’s exact test was used, with effect size by odds ratio (RC). Approved by the Research Ethics Committee under opinion number 4.578.896. Results: The prevalence of stress was 52.7%. The predictors associated with stress were: fear of being a vehicle of infection (RC=4.15;95%CI=1.09;15.76;p=0.04); conflict in work team (RC=2.36;95%CI=1.20;4.66;p=0.02); family conflict (RC=4.03;95%CI=1.96;8.28;p<0.001); doubting their pandemic preparedness (RC=6.17;95%CI=1.70;22.39;p=0.01); thinking it likely to get Covid (RC=2.38;95%CI= 1.07;5.28;p<0.05); being suspected or confirmed for covid-19 (RC=2.14;95%CI= 1.03;4.46;p<0.05); unavailability of Personal Protective Equipment (RC=8.63;95%CI=1.90;39.26;p<0.001); being involved in institution decision making (RC=2.23;95%CI=1.14;4.35;p=0.02); anxiety at being with covid patient (RC=3.43; 95%CI=1.70;6.91;p<0.001); exhaustion at the end of a work day (RC=10.64;95%CI=3.01;37.56;p<0.001); impaired sleep quality or increased anxiety (RC=3.11;95%CI=1.54;6.29;p<0.001). Conclusion: It was verified that more than half of the nursing technicians presented stress, being some of the predictors the high workload, the fear of infection or family members, and the loss in quality of life.